What is the structural chemistry of the living organism at its temperature and pressure?. Issue 2 (10th February 2020) - Helliwell, John R.
Abstract : The three probes of the structure of matter (X‐rays, neutrons and electrons) in biology have complementary properties and strengths. For the study of combined states of order and disorder, NMR crystallography is also applicable. Overall, to understand a biological system, the requirements are physiologically relevant results. Reporting of protein crystal structures, and their associated database entries, could usefully indicate how close to the biological situation they are. Abstract : The three probes of the structure of matter (X‐rays, neutrons and electrons) in biology have complementary properties and strengths. The balance between these three probes within their strengths and weaknesses is perceived to change, even dramatically so at times. For the study of combined states of order and disorder, NMR crystallography is also applicable. Of course, to understand biological systems the required perspectives are surely physiologically relevant temperatures and relevant chemical conditions, as well as a minimal perturbation owing to the needs of the probe itself. These remain very tough challenges because, for example, cryoEM by its very nature will never be performed at room temperature, crystallization often requires nonphysiological chemical conditions, and X‐rays and electrons cause beam damage. However, integrated structural biology techniques and functional assays provide a package towards physiological relevance of any given study. Reporting of protein crystal structures, and their associated database entries, could usefully indicate how close to the biological situation they are, as discussed in detail in this feature article.